1999
DOI: 10.2466/pr0.1999.84.2.517
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Cognitive Changes in Intimacy in Long-Term Romantic Relationships

Abstract: Individuals in Western societies generally look to their romantic partner to meet most of their intimacy needs. However, the level and the nature of the intimacy that partners share varies over the years and over the significant events they experience. Drawing from the literature, this is a review that integrates two approaches to understanding the cognitive changes in intimacy that occur over the course of long-term romantic relationships. It may be helpful for practitioners to teach partners how to identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Our assessment of intimacy in this study was as a reciprocal variable where participants reported on both their own perceptions of the relationship and what they believed to be their partners' perceptions of the relationship. Other researchers have reported on the importance of assessing intimacy in this way (Santore, 2008;Schwebel et al, 1999). Because both theory and empirical data support a linear increase in levels of intimacy (Solomon & Knobloch, 2004), we expected to find the same pattern.…”
mentioning
confidence: 51%
See 2 more Smart Citations
“…Our assessment of intimacy in this study was as a reciprocal variable where participants reported on both their own perceptions of the relationship and what they believed to be their partners' perceptions of the relationship. Other researchers have reported on the importance of assessing intimacy in this way (Santore, 2008;Schwebel et al, 1999). Because both theory and empirical data support a linear increase in levels of intimacy (Solomon & Knobloch, 2004), we expected to find the same pattern.…”
mentioning
confidence: 51%
“…An important contextual characteristic of romantic relationship development is the duration of the relationship, which may have important implications for the ways in which conflict and intimacy are experienced (Dainton & Aylor, 2002;Murray & Holmes, 1996;Shulman & Seiffge-Krenke, 2001;Schwebel et al, 1999). Knobloch (2001, 2004) have proposed the relational turbulence model which suggests that relationships experience a disruption in previously well-working or smooth patterns of interaction; this disruption is labeled relational turbulence.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The scales used to measure intimacy have been quite variable (for reviews, see Moss and Schwebel (1993) and Schwebel et al (1999)). Some intimacy scales include items intended to measure physical interaction and/or sexual satisfaction; for example, one item eliciting information about satisfaction Downloaded by [Fresno Pacific University] at 19:45 20 December 2014 with sex and two other items with the word "physical" are included in the Tesch Psychosocial Intimacy Questionnaire (Tesch, 1985).…”
Section: Intimacymentioning
confidence: 99%
“…Uncertainty has been found to be associated with the quality and stability of romantic relationships (Parks & Adelman, 1983;Planalp, Rutherford, & Honeycutt, 1988;Schwebel, Moss, & Fine, 1999;Siegert & Stamp, 1994) indicating the frequency with which respondents felt able to predict their partners' behavior (1=Never, 5=Very often). Five items were recoded so that higher scores reflect higher levels of uncertainty.…”
Section: Methodsmentioning
confidence: 99%